What is Modern: discourse on modernization as way of self-comprehension of Modern - Levytskyi, Victor (Skhid, 2015)
In the article an attempt of inteprepretation the discourse about modernization as a way of self-understanding the Modern is being made. Importance of this way, which at the time of postmodernist denial of universal ways of cognition appears as one of a few legitimate variants of rational comprehension of the Modern, is being marked. However, the analysis of several authoritative concepts in this sphere allows to come to a conclusion that Modern is a local cultural formation, expansionist ideology of which doesn't turn non-Modern states into new regions of Modern, but directs their development to the path of satellites of Modern.